Incredible Years parenting programme: cost-effectiveness and implementation. Issue 1 (21st March 2016) - Edwards, Rhiannon Tudor; Jones, Carys; Berry, Vashti; Charles, Joanna; Linck, Pat; Bywater, Tracey; Hutchings, Judy
Abstract : Purpose: – There is growing interest in the economic evaluation of public health prevention initiatives and increasing government awareness of the societal costs of conduct disorder in early childhood. The purpose of this paper is to investigate the cost-effectiveness of the Incredible Years (IY) BASIC parenting programme compared with a six-month waiting list control. Design/methodology/approach: – Cost-effectiveness analysis alongside a pragmatic randomised controlled trial of a group-parenting programme. The primary outcome measure was the Strengths and Difficulties Questionnaire (SDQ), a measure of child behaviour. Findings: – The IY programme was found to have a high probability of being cost-effective, shifting an additional 23 per cent of children from above the clinical concern to below the cut-off on the SDQ compared to the control group, at a cost ranging from £1612-£2418 per child, depending on the number of children in the group. Originality/value: – The positive findings of this study have led to ongoing implementation of the IY programme and is therefore an example of commitment to evidence-based service provision and investment in prevention initiatives.